Advanced Biventricular Heart Failure due to Left Ventricular Noncompaction Cardiomyopathy Leading to the Formation of a Gastric Bezoar: The Implications of Heart Failure on the Gastrointestinal Tract. (1st October 2018) - Yunina, Daria; Sharma, Dikshya; Fazio, Richard; Amin, Hossam; Tsirlin, Yuriy; Shetty, Vijay
Abstract : Congestive heart failure (CHF) is a chronic disease process affecting multiple organ systems and is associated with significant morbidity and mortality. We report a case of a 43-year-old male with a history of unspecified cardiomyopathy who presented to the hospital with abdominal pain, distention, and nausea for 4 months. He was diagnosed with left ventricular noncompaction and gastroparesis. While symptoms of dyspnea, orthopnea, or increasing peripheral edema are the first that come to mind when thinking of a CHF exacerbation, we must broaden our scope to include such things as nausea, vomiting, abdominal pain, and bloating which can also indicate worsening cardiac function. This case report highlights the significant yet often forgotten gastrointestinal (GI) symptoms that result from advanced biventricular heart failure, with emphasis on impaired gastric and intestinal motility.